The Contribution of CD40/CD40L Axis in Inflammatory Bowel Disease: An Update - Senhaji, Nezha; Kojok, Kevin; Darif, Youssef; Fadainia, Christophe; Zaid, Younes (Frontiers in Immunology, 2015)
Inflammatory bowel disease (IBD) is a chronic and multifactorial disease of the gastrointestinal tract. The exact etiology of IBD remains complex and unclear involving an inadequately defined relationship between microbial insult, genetic predisposition, altered intestinal barrier permeability, oxidative stress components and abnormal immune responses. The role of the co-stimulatory system made up of cluster of differentiation 40 protein (CD40) and its ligand (CD40L) in the response of the immune system to pathogens is now widely accepted. The implication of CD40/CD40L axis in immune system disorders due to its important role as signal transduction pathway among immune cells is well documented. Several studies have suggested that CD40/CD40L interactions regulate oxidative stress; this can affect various signaling pathways leading to IBD development. Hence, CD40/CD40L signaling pathway may become a new target for IBD treatment. This review will cover the general contribution of the CD40/CD40L dyad in the development of inflammatory bowel disease, in order to facilitate future approaches aiming to elucidate the immunological mechanisms that control gut inflammation.